2005
DOI: 10.1029/2005ja011018
|View full text |Cite
|
Sign up to set email alerts
|

Are sawtooth oscillations of energetic plasma particle fluxes caused by periodic substorms or driven by solar wind pressure enhancements?

Abstract: [1] Energetic electron and proton fluxes measured by geosynchronous satellites often show sawtooth-like variations during magnetic storms. We examine whether the sawtooth oscillations and relevant magnetospheric-ionospheric disturbances are caused by periodic substorms or driven by a series of enhancements in the solar wind pressure. We show that there are significant differences between periodic substorms and solar wind-induced variations. The energetic fluxes at geosynchronous orbit may increase by orders of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 43 publications
4
41
0
Order By: Relevance
“…modulations of the solar wind dynamic pressure (Lee et al, 2004) and northward turnings of the IMF (Lyons et al, 2005). However, the evidence for these hypotheses has been disputed (Huang et al, 2005;. We therefore ask whether the observed periodicities are consistent with an untriggered substorm model, like the MSM.…”
Section: Model Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…modulations of the solar wind dynamic pressure (Lee et al, 2004) and northward turnings of the IMF (Lyons et al, 2005). However, the evidence for these hypotheses has been disputed (Huang et al, 2005;. We therefore ask whether the observed periodicities are consistent with an untriggered substorm model, like the MSM.…”
Section: Model Resultsmentioning
confidence: 89%
“…So that signatures due to solar wind dynamic pressure increases were excluded the flux increase had to be preceded by a gradual decrease in particle flux-this is indicative of substorm growth phase (e.g. Huang et al, 2005)-and not coincident with a large, abrupt solar wind pressure increase. Further, we required that the injection signature was observed within AE3 h of local magnetic midnight.…”
Section: Article In Pressmentioning
confidence: 98%
“…These three studies support the response <1 hour. Other work by Huang et al (2005) reported substorm recurrence periods of a few hours during continuous southward IMF, which could be related to the long term (∼hours) effect of IMF. This analysis certainly suggests follow-up analysis to answer significant questions.…”
Section: Statistical Studies On Imf B Z Dependencementioning
confidence: 92%
“…Nevertheless, EFW worked well during this orbit. This period corresponds to a major storm with sawtooth signatures (e.g., Huang et al 2005;Ohtani et al 2007). In Fig.…”
Section: Inner Magnetospheric Electric Field (Unh-imef) Modelmentioning
confidence: 98%